Grand Designs : Labor, Empire, and the Museum in Victorian Culture - Kriegel, Lara, 1968- (Book collections on Project MUSE., 2007)
"Grand Designs is a study of the politics of cultural production in early and mid-Victorian Britain. Kriegel's interpretation revises what has been the dominant account in design culture of "a spectacular modernity characterized by commodity display and consumerism," an interpretation that reifies the place of machinery and machine production in exhibits. Kriegel demonstrates both the centrality of artisanal labor in exhibition culture and the deeply contested nature of design reform. Close readings of an extraordinary cache of visual and literary representations plumbed from contemporary journals and newspapers wonderfully illuminate the discourse of design reform as it emerged in the Great Exhibition of 1851 and at the South Kensington Museum."--Jacket.